A study of metaverse acceptance among Malaysian undergraduate media students based on the technology acceptance model - Sim, Aloysius Jing Xian (2023)
Facebook’s shift to focus on metaverse development and its rebranding into Meta has brought about a wave of discussion on the possibilities of the metaverse in various industries. While the term “metaverse” has been used in several fictional works and throughout the development of virtual reality and augmented reality, Meta’s vision is one that has triggered the metaverse trend. As with all technological advancements, researchers are interested in users’ acceptance of this new technology. Current academic papers have discussed the metaverse technology in medicine, education as well as general day-to-day use. However, at the time of writing, there have been no academic discussions on how the metaverse is being accepted by undergraduate media students in Malaysia based on the Technology Acceptance Model (TAM). Hence, this study aims to investigate Malaysian undergraduate media students’ awareness of metaverse development, examine their attitude toward metaverse technology and investigate the relationship between their attitude and behavioural intention to use metaverse technology based on the TAM. This study will employ a quantitative method by distributing 50 sets of questionnaires to undergraduate media students in universities within the Klang Valley through Google Forms. The collected data was analysed through Statistical Package for the Social Sciences (SPSS). Results found positive correlations between perceived ease of use and perceived usefulness, attitude towards technology use and behavioural intention. However, a weaker correlation exists between perceived ease of use and attitude toward technology use. The findings provide a precedent for educators and relevant corporations to understand media students’ attitude of acceptance towards the metaverse.